2014
DOI: 10.1111/vox.12098
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial contamination in platelet concentrates

Abstract: whole-blood-derived PCs and apheresis PCs are stored up to 5 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 30 publications
1
71
1
1
Order By: Relevance
“…Noteworthy, bacterial screening and pathogen inactivation are handled quite differently in various countries (Pietersz et al, 2014).…”
Section: Iccvam Recommendations For Future Mat Validation Studies Maymentioning
confidence: 99%
“…Noteworthy, bacterial screening and pathogen inactivation are handled quite differently in various countries (Pietersz et al, 2014).…”
Section: Iccvam Recommendations For Future Mat Validation Studies Maymentioning
confidence: 99%
“…We also appropriately increased residual risk of platelet bacterial contamination to account for large differences in safety measures between the two countries. The reporting of high rates of detection of bacterial contamination in all three labile components in similar settings, as described by studies performed in Germany and Croatia [19][20][21], does not reconcile easily with very low rates of adverse events in hemovigilance data [22]. By varying, simultaneously, the probability of contamination in plasma products and death due to sepsis, we showed that a specific joint probability of death from sepsis may lead to disparate ICERs in our model.…”
Section: Discussionmentioning
confidence: 49%
“…However, platelet concentrates expire for transfusion purposes after a maximum shelf-life of 5 days, after which they can still be used as a cell culture supplement. Since platelet concentrates are stored at room temperature, there is a risk of bacterial contamination (Pietersz et al, 2014). Thus, the shelf-life (in Germany) is currently restricted to 4 days and can be extended to 5 days in case of negative bacterial testing.…”
Section: Alternatives To Fbsmentioning
confidence: 99%